Indonesian Foreign Policy in the Era of Susilo Bambang Yudhoyono (2004-2014) towards Myanmar in Supporting Democratization - Windy Dermawan; Chandra Purnama; Emil Mahyudin (Jurnal Hubungan Internasional, 2018)
This research attempts to answer the question of why Indonesia supported democratization in Myanmar. In this research, researchers use the constructivism perspective to analyze Indonesia's foreign policy by exploring Indonesia's reasons for promoting democratization in Myanmar. This motivation becomes an interesting thing when Indonesia's reason is more of nonmaterial than material. This research uses qualitative methods by collecting data through interviews with a number of informants and documentation studies. Based on the results of data analysis, this research has found that Indonesia's foreign policy toward Myanmar in supporting democratization is based on consideration of domestic, regional and global ideas, values or norms. These norms and ideas are constructed so as to encourage the formation of an Indonesian identity which is the basis for the production and reproduction of Indonesia's interests in Myanmar in promoting democratization. Indonesia's desire to re-hold regional leadership, the restoration of its image as a democratic country, and a commitment to maintain world peace are part of the production and reproduction of discourses on Indonesia's interests which contribute to the formation of Indonesia's foreign policy towards Myanmar.